Geological Risk Assessment, Environmental Management Practices, and Sustainable Mining Operations: Evidence from a Survey-Based SEM-PLS - Obed Patiung; Restyana Aulya; Zahwa Paewa (International Journal of Hydrological and Environmental for Sustainability, 2026)
The mining industry faces significant challenges in maintaining sustainable operations due to geological uncertainty, environmental degradation, and increasing demands for effective environmental management. Geological hazards such as slope instability, landslide potential, groundwater inflow, mine drainage problems, erosion, and waste rock instability may directly affect environmental quality and operational sustainability. This study examines the relationships among Geological Risk Assessment (GRA), Environmental Management Practices (EMP), and Sustainable Mining Operations (SMO) using survey responses from 150 mining professionals in Indonesia, covering coal, nickel, copper, and gold mines. A cross-sectional survey design and Structural Equation Modeling–Partial Least Squares (SEM-PLS) were applied to assess the associations among GRA, EMP, and SMO and to evaluate the mediating role of EMP. The results indicate that GRA is positively associated with EMP (β = 0.718) and SMO (β = 0.402), while EMP positively affects SMO (β = 0.424). EMP also partially mediates the relationship between GRA and SMO, with an indirect effect of β = 0.305. These findings suggest that geological risk assessment contributes to sustainable mining by strengthening environmental management practices, particularly in relation to mine water management, erosion control, land reclamation, waste management, and environmental impact monitoring. The study provides a conceptual SEM-PLS model linking geological risk, environmental management, and sustainable mining performance, offering practical insights for improving environmentally responsible mining operations in Indonesia.